IDENTIFIKASI MOLEKULER VIRUS INFECTIOUS BURSAL DISEASE DENGAN METODE REVERSE TRANSCRIPTASE POLYMERASE CHAIN REACTION - , CHOIRUN NISWAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Infectious bursal disease (IBD) is a viral disease that caused by double strand RNA (dsRNA) virus that derived from Birnaviridae family. The disease is well known as Gumboro has infected lymphoid tissue of 3-6 weeks old young chicken, especially on bursa of Fabrisius. Gumboro cause a huge economic loss in the poultry industry, examples increasing the mortality and morbidity in chickens due to the immunosuppressive effects, therefore, early detection of IBD virus is necessary to prevent spreading of IBDV. A moleculer techniques that have been frequently used to detect IBDV is Reverse Transcriptase Polymerase Chain Reaction (RT-PCR), RT-PCR method was choosen due to highly sensitifity and accurate than the convensional methods such as ELISA and AGPT. This research aims to identify IBDV with one-step RT-PCR method. The tested tissue used in this research were isolate IBD virus chorioallantois membrane (MHW/Yanti/Layer/2011 isolate and MHW/Bro/2012 isolate) and samples of bursa of Fabrisius (MHW/SR-A, MHW/SR-B, MHW/N18/15-4-2014, MHW/N18/14-4-2014, MWH/N1/15-4-2014 and MHW/NF/2014). Firstly, the samples dan isolates were made into suspension, then the suspension were extracted to obtain RNA using Extraction RNA kit from GeneAid and then perform the RT-PCR using RT-PCR kit Invitrogen with the forward primer (5´-GTCTACACCATAACTGCCGCAGATGAT-3´) and reverse primer (5´-GGCTACTAGTGTGACGGGGCGGAGGGCACC-3´) that will amplify VP2 gene of IBD virus and giving product of 440 bp. The results of RTPCR were read using 1.5% agarose gel electrophoresis. The results of thus research showed two isolates (MHW/Yanti/Layer/2011 isolate and MHW/Bro/2012 isolate) were positive infected by IBDV while six samples were negative (MHW/SR-A, MHW/SR-B, MHW/N18/15-4-2014, MHW/N18/14-4-2014, MWH/N1/15-4-2014 and MHW/NF/2014). Positive results on agarose gel electrophoresis was showed by giving product of 440bp.